Internet use and need for digital health technology among the elderly: a cross-sectional survey in China - Sun, Xinran (BMC Public Health, 2020)
BACKGROUND: China is becoming an aging society at the fastest pace in history, and there are a large number of empty nesters in the country. With economic and social development, internal support systems among families are gradually weakening. Supporting the elderly is thus emerging as a significant issue, and promoting digital health technologies is an effective way to help address it. Encouraging the application of Internet to elderly care and Internet use among the elderly are important means of promoting digital health technologies. This paper examines the current state of the use of the Internet by the elderly and factors influencing it (including physical, psychological, and social) as well as demand among the elderly for smart services. METHODS: A total of 669 subjects over the age of 60 years were randomly selected from 13 cities in Heilongjiang province and surveyed using questionnaires from May 1 to July 31, 2018. The questionnaires were collected for descriptive statistics, the chi-square test, and the analysis of influential factors. RESULTS: Of the people surveyed, 38.6% used the Internet. Their favorite online activity was online dating (74.2%), and the health information they obtained through the Internet was mainly related to diet (63.1%) and exercise (47.1%). The subjects demanded smart bracelets (MD = 2.80) and emergency callers (MD = 2.77). Gender, age, education, monthly income, quality of life, number of friends, and social participation were found to have an impact on Internet use. CONCLUSIONS: More measures are needed to reduce barriers to the use of the Internet and promote digital health technologies. The society, equipment manufacturers, and family members of the elderly should work together to enable them to reap the benefits of online technologies.